1998
DOI: 10.1083/jcb.142.4.1075
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Corepressor NAB2 Inhibits NGF-induced Differentiation of PC12 Cells

Abstract: The PC12 pheochromocytoma cell line responds to NGF by undergoing growth arrest and proceeding to differentiate toward a neuronal phenotype. Among the early genetic events triggered by NGF in PC12 cells are the rapid activation of the zinc finger transcription factor Egr1/NGFI-A, and a slightly delayed induction of NAB2, a corepressor that inhibits Egr1 transcriptional activity. We found that stably transfected PC12 cells expressing high levels of NAB2 do not differentiate, but rather continue to proliferate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…PKC-dependent EGR-1 activation has been implicated in some other cell types in differentiation processes. Examples are the nerve growth factor-induced differentiation of nerve cells and the IL-3 and GM-CSF-triggered differentiation of hematopoietic progenitor cells (9,10). In regard to angiogenesis, it is possible that sprouting and tube formation starting from mature endothelial cells include regulatory mechanisms similar to angioblast differentiation (2), and there is further evidence that the recruitment of angioblasts from the circulation and their differentiation plays a role for vessel formation in the adult.…”
Section: Nab2 Overexpression By Recombinant Adenoviruses Inhibits Indmentioning
confidence: 99%
See 2 more Smart Citations
“…PKC-dependent EGR-1 activation has been implicated in some other cell types in differentiation processes. Examples are the nerve growth factor-induced differentiation of nerve cells and the IL-3 and GM-CSF-triggered differentiation of hematopoietic progenitor cells (9,10). In regard to angiogenesis, it is possible that sprouting and tube formation starting from mature endothelial cells include regulatory mechanisms similar to angioblast differentiation (2), and there is further evidence that the recruitment of angioblasts from the circulation and their differentiation plays a role for vessel formation in the adult.…”
Section: Nab2 Overexpression By Recombinant Adenoviruses Inhibits Indmentioning
confidence: 99%
“…Major signals induced by VEGF via VEGFR-2 in endothelial cells include activation of the phosphoinositol 3-kinase/PKB and phospholipase C-␥/PKC pathways (4,5). Whereas activation of PKB has been primarily implicated in cell survival (6), recent in vitro studies have shown that VEGF treatment of endothelial cells leads to a PKC-dependent activation of the MEK/ERK module of MAP kinases resulting in a rapid up-regulation of the transcription factor EGR-1 (7,8), which has been associated with growth and differentiation of various cell types (9,10). Furthermore, EGR-1 is critically involved in the up-regulation of genes such as tissue factor (TF) (7,8), VEGF receptor-1 (VEGFR-1) (11,12), and urokinase-type plasminogen activator (uPA) (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-cell lysates (50 g total protein per sample) were separated by SDS-PAGE and transferred to nitrocellulose membranes (Schleicher & Schuell, Keene, NH). Membranes were blocked for 1 hour at room temperature with 1% skim milk in PBS containing 0.1% (v/v) Tween 20 (PBS-T) and then incubated for 1 hour at room temperature with diluted rabbit polyclonal anti-EGR-1 (Santa Cruz Biotechnology, Santa Cruz, CA), 38 mouse monoclonal anti-HIF-1␣ (Santa Cruz Biotechnology), 39 rabbit polyclonal anti-VEGF-A (Santa Cruz Biotechnology), 11,40 mouse monoclonal anti-NAB-2 (Santa Cruz Biotechnology), 41 or rabbit polyclonal anti-NAB-1 (AVIVA Systems Biology, San Diego, CA). 26 After washing three times with PBS-T at room temperature, membranes were incubated at room temperature for 30 minutes with diluted peroxidase-labeled anti-rabbit or anti-mouse secondary antibody (Amersham Biosciences, Buckinghamshire, UK).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…EGR1, a prototype of the family, has been reported to be induced by diverse stimuli, including the addition of mitogens (Gashler & Sukhatme 1995), and is considered to be involved in either cell proliferation or differentiation in a variety of tissues and cell lines. For example, EGR1 was reported to be essential for the transcriptional autoregulation of basic fibroblast growth factor (bFGF) in hepatoma cells (Wang et al 1997), and in the case of PC12 cells, EGR1 was considered to be involved in differentiation induced by nerve growth factor (NGF), and the overexpression of cofactor NAB2 inhibited differentiation of the cells (Qu et al 1998). EGR3 was also reported to be induced by various stimuli, a large number of which were the same as the case of EGR1 (O'Donovan et al 1998, Mercier et al 2001, Jouvert et al 2002.…”
Section: Introductionmentioning
confidence: 99%